Refleksi Qs. Ar-Ra'du: 11 Dan Qs. Al-Anfal: 53 Self Awareness Sebagai Kesalehan Sosial - Imam Syafi'i; Komarudin Sassi (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo Indonesia, 2025)
This paper reviews the relationship between self-awareness and the formation of social piety, with reference to reflection on QS. Ar-Ra'd verse 11 and QS. In the reality of today's Muslim society that is experiencing moral and spiritual challenges, self-awareness can be used as foundation in building individual character who are socially and spiritually responsible. Through qualitative research methods and a muqaran (comparative) tafsir approach, this study explores that individual transformation is a prerequisite for better social change. QS. Ar-Ra'd verse 11 highlights the urgency of internal change as the key to creating collective change, while QS. Al-Anfal verse 53 emphasizes the importance of preserving Allah's blessings with constant self-awareness. Reflection on these two verses confirms that strengthening spiritual values through character education is essential, not only for the general public, but also for religious leaders, academics and those with social influence. This study recommends that the value of self-awareness be thoroughly integrated in the Islamic religious education curriculum, in order to form a society with pious, just and dignified characters. Keywords: Self-awareness, social piety, QS. Ar-Ra'd: 11, QS. Al-Anfal: 53, individual transformation, Islamic character education